Dexmedetomidine in oxycodone patient-controlled analgesia after lumbar spinal fusion: A randomized, double-blind, placebo-controlled trial - Mäkelä, Sanna; Gröhn, Janne; Rantakokko, Juho; Löyttyniemi, Eliisa; Peltoniemi, Marko; Aantaa, Riku; Liukas, Antti; Saari, Teijo; Uusalo, Panu (Elsevier, 2026)
Background: Spinal fusion surgery causes severe postoperative pain often managed with strong opioids, which may lead to adverse effects. Dexmedetomidine is a potential adjuvant in opioid patient-controlled analgesia (PCA), but the optimal dose remains unclear.
Methods: In this double-blind, placebo-controlled trial, adult patients undergoing major lumbar spinal fusion were randomized to receive placebo (D0) or dexmedetomidine at 2.5 (D2), 5 (D5), or 10 μg/ml (D10) combined with oxycodone (1 mg/ml) PCA for 24 h, followed by oxycodone alone for 48 h. The primary outcome was cumulative oxycodone consumption at 24 h.
Results: Ninety-eight patients were included in the final analysis. Unadjusted postoperative opioid consumption was lower in D10 at 1 h (mean difference 3.1 mg, 95% CI 0.6-5.9, p = 0.011) and at 2 h (3.7 mg, 95% CI 0.5-6.9 mg, p = 0.019) and in D5 at 2 h (3.5 mg, 0.3-6.9 mg, p = 0.027) compared with control group D0. No differences were found in cumulative consumption at 24 or 72 h. When 24-h postoperative opioid consumption was adjusted with age and weight, the results remained unchanged. Compared with D0, patients receiving dexmedetomidine had less postoperative nausea and vomiting (p = 0.04) and itching (p = 0.024) at 24 h. Adverse events and patient satisfaction were otherwise comparable.
Conclusion: Adding dexmedetomidine to oxycodone PCA provided modest early opioid-sparing effects without reducing 72-h opioid consumption. The main benefit was improved 24-h tolerability, with fewer opioid-related side effects. Dexmedetomidine may therefore serve as a useful adjunct in patients at risk of opioid-induced adverse events after lumbar fusion surgery.